2019
DOI: 10.1016/j.omtm.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Lentiviral Transduction of Human CD34+ Cells in High-Density Culture with Poloxamer and Prostaglandin E2

Abstract: Hematopoietic stem cell (HSC) gene therapy is curative for various hereditary diseases; however, high-efficiency transduction in HSCs remains crucial to improve the prospects for hemoglobinopathies. We previously optimized lentiviral transduction in human CD34+ cells with serum-free medium containing minimal cytokines, allowing efficient transduction (∼50%) and robust xenograft engraftment. In this study, we further improved lentiviral transduction in human CD34+ cells. High-density culture conditions (4e6/mL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…PGE2 acts by enhancing intracellular cAMP leading to an improvement in viral transduction. The combination of these two molecules (P407 and PGE2) has been previously shown improve lentiviral transduction in CD34+ cells with high-efficiency and without significant cytotoxicity ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…PGE2 acts by enhancing intracellular cAMP leading to an improvement in viral transduction. The combination of these two molecules (P407 and PGE2) has been previously shown improve lentiviral transduction in CD34+ cells with high-efficiency and without significant cytotoxicity ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…9). In addition, we recently demonstrated more efficient transduction methods in human CD34 + cells in high-density culture with adjuvants 47 . Improvement of transduction efficiency and transgene expression might allow for higher amounts of human β-globin production at the protein level in transplanted rhesus macaques and, ultimately, in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Among the tested three combinations, the one with the lowest content of cytokines showed the highest VCN and maintained the highest CD34+ percentage following LV transduction ( Figure 3A). Second, we assessed distinct transduction enhancers, including protamine, dmPGE2, UM171, and Poloxamer407 [40][41][42] and tested their individual or combinational effects on LV transduction in mPB HSCs. We found that dmPGE2 and Poloxamer407 combination (PGE-Pol) was the most efficient, which increased the VCN by 6-7 times when compared with enhancer free control ( Figure 3B).…”
Section: Optimization Of Lentiviral Transduction In Mobilized Periphementioning
confidence: 99%